2014
DOI: 10.1186/1471-2458-14-892
|View full text |Cite
|
Sign up to set email alerts
|

Violence and reproductive health preceding flight from war: accounts from Somali born women in Sweden

Abstract: BackgroundPolitical violence and war are push factors for migration and social determinants of health among migrants. Somali migration to Sweden has increased threefold since 2004, and now comprises refugees with more than 20 years of war experiences. Health is influenced by earlier life experiences with adverse sexual and reproductive health, violence, and mental distress being linked. Adverse pregnancy outcomes are reported among Somali born refugees in high-income countries. The aim of this study was to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(105 citation statements)
references
References 46 publications
1
102
0
2
Order By: Relevance
“…The present study was part of a larger data collection also including Somali born women’s perspectives [ 37 ]. Data were collected in 2012 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was part of a larger data collection also including Somali born women’s perspectives [ 37 ]. Data were collected in 2012 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…In East and Central Africa, women reported that disclosure could reduce women’s marriage prospects and increase the likelihood of mistreatment and stigmatization by family and community members (Byrskog, Olsson, Essen, & Allvin, 2014; Kelly et al, 2012). Boys may not disclose SV because of norms around masculinity (Easton, 2014), which expect them to resist sexual advances or to deal with the abuse on their own (Donnelly & Kenyon, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While the expansion of antiretroviral therapy in sub‐Saharan Africa has contributed to reductions in the incidence of HIV/AIDS in Africa (Delva & Abdool Karim, ), more work is needed to improve our understanding of factors influencing higher HIV rates in younger African women (Roxby et al, ). Several studies have associated HIV risk in African women with stigma, silence, and shame, especially among those who also experience sexual abuse (Byrskog, Olsson, Essén, & Allvin, ; Loutfy et al, ; Sprague, Hatcher, Woollett, Sommers, & Black, ).…”
Section: Introductionmentioning
confidence: 99%